Mental Health Conditions, Substance Use Disorders, and Jail Readmission in Four Rural Counties - Singer, Alexa J. (International journal of offender therapy and comparative criminology, 2025)
Most jails are in rural areas, and many adults who pass through these facilities experience behavioral health needs. Evidence suggests mental health conditions (MHCs) and substance use disorders (SUDs) may be linked to an increased risk for jail readmission, but most work documenting this relationship uses vague measures, outdated diagnostic information, has been conducted in large metropolitan jails, or has demonstrated significant variability between facilities. This multisite study examined the associations between specific MHCs, SUDs, and jail readmission among 675 adults from four rural jails. Descriptive statistics and multivariate analyses indicated rural jail populations are likely to present MHCs, especially major depression and PTSD, at higher rates than those found in national estimates. SUDs were also observed at rates higher than those typical of national surveys, and particular SUDs were significantly more prevalent in some facilities relative to others. MHCs were not associated with prior jail admission, but SUDs were linked to a greater probability of a previous jail stay. These results highlight the importance of increasing the availability of jail-based, substance-specific treatment programs that cater to individual facilities’ most pressing needs to ultimately reduce jail readmission.